A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa - Zettler, Michael L.; Myers, Alan (Zootaxa, 2018)
A new species of kamakid amphipod, Ledoyerella kunensis sp. nov., is described from waters off Namibia and Angola. This is the first record of this genus in the Atlantic. The taxon is fully described and figured and is compared with the other known species of the genus occurring in waters of the Indian and Pacific Ocean.